Paternidade e maternidade na adolescência: produção de saberes e sentidos compartilhados por adolescentes - Souza, Andréa Xavier de Albuquerque de (2013)
The present study aimed to identify the social representations made by adolescent fathers and mothers on paternity and motherhood in adolescence. Recognizing the importance of integrating the teenage father in the process of paternity, this research has included in its scope the male adolescent. This study was supported on the Social Representations Theory. With the participation of 80 teenagers distributed equitably by gender, from lower social classes, ages from 14 to 19 years-old (M = 16.71, SD = 1.20), who pass through the experience of having only one child. To collect data, it was used a multimethod approach, counting on different instruments: Questionnaire on bio-socio-demographic characteristics and contraceptive practices which answers were recorded in PASW (Predictive Analytics SoftWare) version 18, and analyzed by descriptive statistics; free word association test, processed in software Tri-Deux Mots for Correspondence Factor Analysis (CFA) and; Semi-structured Interview, which was submitted to the Alceste software for the analysis of descending and ascending hierarchical classifications. The results of the CFA showed that adolescents have representations that vary according to gender. Teenager parents represented paternity as "learning", an experience that generates demands from the need to "help", causing a "loss of freedom". The adolescent mothers indicated some assignments in which the parent is negatively associated to that which "does not accept the child" and seems "irresponsible", and should take help in child rearing, which was objectified in the expression "must participate". Motherhood in adolescence, according to male participants, was objectified in the practice of "breastfeeding", considered by them as a symbolic feature of this experience, was also associated with affective aspect "give love" and to the commitment of "taking care of the child". For its time, the mothers objectified experience of motherhood with a positive connotation associated with "something good", representing "love", a "dream", a "God thing", but, nevertheless, recognize that "demands responsibility" before the role of "caring" son. The analysis of the interviews revealed a dendrogram structured by four thematic classes whose representational contents are associated to the experiences and meanings of parenthood in adolescence, including aspects of the difficulty of inserting paternal and maternal commitment; to the knowledge about contraception, their means of serving and preventive practices; to the future projects planned before and after being fathers/ mothers, and, finally, to the affects mobilized forward to pregnancy and judgment of another. It is hoped that the knowledge produced in this research allows broaden discussions and reflections around the studied object, providing information on the beliefs, attitudes, images, opinions and meanings of adolescents. In this respect, it trusts that the findings of this thesis may shed light on the knowledge produced by teenagers, especially in the father s perspective, in order to insert them into public policies on health and sex education to enable them to engage in this process, deconstructing the idea of social invisibility commonly associated with the father figure in the affective experience of having/ caring for a child in adolescence.